Analysis and Simulation of VLAN Using Cisco Packet Tracer - Rajni Ingale; Sushil Bakhtar (International Journal of Satellite Remote Sensing, 2024)
The acronym for Virtual Local Area Network, or Virtual LAN, is VLAN. We build this unique network from one or more pre-existing LANs. In order to provide scalable, dependable, and secure services regardless of location, today's networks must always be accessible from anyplace. Reducing users and workgroups that are separated is the main objective of a network. Each system must have the ability to interact with other systems and transmit necessary data. In addition, physical systems and equipment must be able to provide sufficient security, dependability, and performance. It makes it possible to unite a collection of devices from several wired and wireless networks into a single logical network. A VLAN that can be managed similarly to a physical area network is the end result. To construct a VLAN, network hardware such as switches and routers has to support VLAN configurations.
Keywords: VLAN; Wi-Fi; cisco packet tracer; networking; wireless networks